Iberian extreme precipitation 1855/1856: an analysis from early instrumental observations and documentary sources. (21st March 2014) - Domínguez‐Castro, F.; Ramos, Alexandre M.; García‐Herrera, Ricardo; Trigo, Ricardo M.
ABSTRACT Flood events is the natural hazard that originated more damages and fatalities in the Iberian Peninsula in the last decades. While most 20th century extreme precipitation and flood episodes in Iberia have been documented, the same does not hold for most events that took place during the 19th century. This article describes the unusually high precipitation and associated impacts recorded during the 1855/1856 hydrological year. We combine newspaper reports, early instrumental precipitation series and sea level pressure (SLP) reconstructed gridded fields. The early instrumental precipitation time series includes 11 observatories that were not previously digitized and preceded the implementation of the official meteorological observation network in Spain. We show that high values of precipitation were mostly recorded during the months of September, October 1855 and January 1856, with most of the flooding and damages occurring in the last month. The use of daily circulation weather types and monthly differences of SLP are particularly useful to explain the heavy precipitation in October and January, which were clearly associated with unusual high frequencies of wet weather types. However, SLP patterns cannot explain the September records, which could be associated to upper cold air intrusions in the Iberian Peninsula.